Analisis Kerjasama Two Countries Twin Parks Indonesia-Tiongkok - Munawaroh, Rina (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
The Twin Parks Cooperation between Indonesia and China is an initiative that aims to develop a dual park area as a symbol of bilateral cooperation in ecotourism development. The concept involves the development of two park sites, one in each country, that are interconnected and designed to promote environmental preservation, sustainable tourism, and cultural exchange between the two countries. The main objectives of the project, the site selection process, the development and management model applied, and the social, economic, and environmental impacts of the Twin Parks implementation. The research method used in this study is qualitative with a comparative case study design by analysing the similarities and differences in the two countries' approaches to the development of Twin Parks. This research illustrates the importance of international co-operation in environmental and tourism management, and provides insights for the further development of bilateral co-operation in the future.